The role of Langerhans cells in etiopathogenesis of atopic dermatitis - Polasik, Kinga; Placek, Waldemar; Romańska-Gocka, Krystyna (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction . Atopic dermatitis (AD) is a very common chronic skin disease which displays many immunological abnormalities, e.g. high concentration of IgE, excessive activity of Langerhans cells (LC), increased expression of CD23 receptor. Langerhans cells are dendritic cells which make up 3-8% of epidermal cells and they are present in higher numbers in persons with allergic diseases. Langerhans cells are able to capture exogenous antigens, such as haptens or viral antigens, transform them and present them to T lymphocytes. On the surface of LC HLA-DR antigens, CD4 antigen, FceRIa and CD 23 receptors, receptors for IgE and CD 1a and co-stimulation molecules CD 80/B7-1 and CD 86/B7-2a are present. Objective . The aim of this study was to establish, using antibodies to CD1a and HLA-DR antigens, the number and morphological features of LC in the epidermis of patients with atopic dermatitis in comparison to healthy controls and to look for FceRIa, CD4, CD23, CD80/B7-1, CD86/B7-2, and IgE receptors on their surface. Material and methods . The study was performed by double staining in immunofluorescence method using labelled immune sera to CD1a, HLA-DR, FceRIa, CD4, CD23, CD80/B7-1, CD86/B7-2, and IgE antigens. Eighteen biopsies from atopic dermatitis patients and, as a control, 10 biopsies from healthy persons were studied. Results . In the epidermis of patients with atopic dermatitis a higher number of CD 1a positive LC in comparison to healthy controls was found and its morphology was different. On the surface of LC in the epidermis of AD patients all studied receptors were present, while in the epidermis of healthy persons only CD1a, HLA-DR and FcεRIα receptors were observed. Conclusion . The role of LC depends on the presence of receptors on their surface. The morphology of epidermal LC cells in atopic dermatitis and in healthy persons is different. The higher number of LC in epidermis of patients with atopic dermatitis may be related to the inflammatory process.